2015
DOI: 10.1097/pts.0000000000000064
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Issues in Patient Safety Research

Abstract: As many as 1 in 10 patients is harmed while receiving hospital care in wealthy countries. The risk of health care-associated infection in some developing countries is as much as 20 times higher. In response, in many global regions, increased attention has turned to the implementation of a broad program of safety research, encompassing a variety of methods. Although important international ethical guidelines for research exist, literature has been emerging in the last 20 years that begins to apply such guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Most importantly, other systematic qualitative reviews of normative information already demonstrated the instrumental value of this approach for a descriptive and stakeholder-oriented analysis and synthesis of normative arguments [18, 19, 28]. Additionally, we found this approach to be more grounded in the actual theoretical discussions in the public health ethics literature than, for example, an approach relying on the authors’ statement in the abstract to discuss ethical issues (which other reviews relied on [48]). Second, we also chose one particular principlist framework over possible alternatives [29].…”
Section: Discussionmentioning
confidence: 70%
“…Most importantly, other systematic qualitative reviews of normative information already demonstrated the instrumental value of this approach for a descriptive and stakeholder-oriented analysis and synthesis of normative arguments [18, 19, 28]. Additionally, we found this approach to be more grounded in the actual theoretical discussions in the public health ethics literature than, for example, an approach relying on the authors’ statement in the abstract to discuss ethical issues (which other reviews relied on [48]). Second, we also chose one particular principlist framework over possible alternatives [29].…”
Section: Discussionmentioning
confidence: 70%
“…D.W. ultimately excluded 12 articles, as they did not meet the aims of this current work on final review." [40] Explanation: In order to synthesize, the extracted data may need some transformation (processing). Authors should report how they planned to evaluate and handle between-study variability (e.g.…”
Section: Entreq)mentioning
confidence: 99%
“…Morality is about the question "what is right?" and about respect for human values, e.g., in bio-medical research: respect for autonomy, non-maleficence, beneficence and justice [19,[34][35][36]. Rahanu et al also mentions fidelity, reparation (undo damage done to others), justice, beneficence, self-improvement, gratitude and non-injury [29].…”
Section: Moral and Ethical Principles In A Range Of Situations In Societymentioning
confidence: 99%